EFFECTS OF ORAL IRON SUPPLEMENT ON BREATH-HOLDING SPELLS IN CHILDREN - TONEKABONI MD, S.H.; ALAVI MD, S.; MAHVELATI MD, F.; TABASI MD, Z. (Iranian Journal of Child Neurology, 2009)
Objectives: Breath holding spells are one of the most frequent and important diagnostic challenges in pediatrics. The aim of this study, conducted on pediatric patients referring to the pediatric neurology clinic in Hormozgan province, was to evaluate therapeutic effects of iron on breath holding spells Materials and Methods: 35 children (19 males and 16 females), aged between 3 to 60 months, with a history of breath-holding spells, were included in the trial. To obtain all relevant data a specifically designed questionnaire requiring information on sex, age, age of onset of spells, type of spells, frequency of attacks before and after treatment with oral iron supplement, and determinants of body iron stores was completed for all the patients, based on the mother's statements. The patients were treated by an oral iron preparation for three months. Results: The age of onset of spells ranged between 6 to 24 months. The cyanotic type of spell was detected in 31 children, the pallid type in 3, and the mixed type in one child. There were 14 children with iron deficiency anemia and 20 children with reduced iron stores. Just one child had a normal iron profile. Complete therapeutic response was documented in 24 children, good response in 9, and poor response in one and in one child no change in frequency of spells was seen. Conclusion: Although no significant therapeutic difference was seen in the different response groups, it seems that iron supplement may play an important role in reducing breath holding spells in children. Keywords: Iron, Breath holding spell, children, Iron deficiency Anemia